Engineering Scalable Manufacturing of High-Quality Stem Cell-Derived Cardiomyocytes for Cardiac Tissue Repair - Dunn, Kaitlin K.; Palecek, Sean P. (Frontiers in Medicine, 2018)
Recent advances in the differentiation and production of human pluripotent stem cell (hPSC)-derived cardiomyocytes (CMs) have stimulated development of strategies to use these cells in human cardiac regenerative therapies. A prerequisite for clinical trials and translational implementation of hPSC-derived CMs is the ability to manufacture safe and potent cells on the scale needed to replace cells lost during heart disease. Current differentiation protocols generate fetal-like CMs that exhibit proarrhythmogenic potential. Sufficient maturation of these hPSC-derived CMs has yet to be achieved to allow these cells to be used as a regenerative medicine therapy. Insights into the native cardiac environment during heart development may enable engineering of strategies that guide hPSC-derived CMs to mature. Specifically, considerations must be made in regards to developing methods to incorporate the native intercellular interactions and biomechanical cues into hPSC-derived CM production that are conducive to scale-up.